ChemInform Abstract: Silver‐Mediated N‐Trifluoromethylation of Sulfoximines. Issue 44 (15th October 2015) - Teng, Fan; Cheng, Jiang; Bolm, Carsten
Abstract A new N‐trifluoromethylation method is developed to give unreported sulfoximine derivatives with good functional group tolerance via a radical process.